Methods of teaching English to young learners - Suyunova, Go’zal (Журнал иностранных языков и лингвистики, 2021)
Annotation: This article is devoted to techniques of teaching English to young learners. Young learners’ interests and their age should be taken int o consideration when choosing teaching strategies. More activities could be used for the purpose of the lesson more fascinating and exciting. The teachers’ techniques in teaching English to young learners were singing a song, games, presentation practice and production, drilling, demonstration, story-telling, reading aloud, and dictation. The best teaching techniques implemented by the teachers were playing games, demonstration and presentation practice and production. Keywords: Young learners, teachers’ techniques, activities, teaching English, recources.